2016
DOI: 10.1007/s13105-016-0496-2
|View full text |Cite
|
Sign up to set email alerts
|

miRNA involvement in angiogenesis in age-related macular degeneration

Abstract: Age-related macular degeneration (AMD) is the leading cause of blindness in the elderly. Late-stage AMD is characterized by choroidal neovascularization (CNV). miR-93 appears to play a role in regulating vascular endothelial growth factor-A (VEGF-A), a known factor involved in neovascularization. Understanding its biological significance might enable development of therapeutic interventions for diseases like AMD. We aimed to determine the role of miR-93 in AMD using a laser-induced CNV mouse model. CNV was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Accumulating evidence indicates that aberrantly expressed miRNAs play important roles in AMD progression (17,19). Given that CXCR7 is an important regulator of angiogenesis, in the current study, we focused on miRNAs that target to CXCR7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence indicates that aberrantly expressed miRNAs play important roles in AMD progression (17,19). Given that CXCR7 is an important regulator of angiogenesis, in the current study, we focused on miRNAs that target to CXCR7.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in animals and humans have revealed important functions of miRNAs in the development and progression of wet AMD (15)(16)(17). Thus far, several miRNAs with proangiogenic (miR- 23, -27, and -155) or antiangiogenic (miR-31, -150, -24, -29, and -93) functions have been identified by using the laser-induced CNV murine model, a wellestablished model that closely mimics the pathogenesis of AMD in humans (18)(19)(20)(21)(22)(23)(24); however, it remains unclear whether other miRNAs, especially those that target to CXCR7, are also involved in the process of angiogenesis in CNV.…”
mentioning
confidence: 99%
“…It is physiologically required for regulating proliferation and assembling endothelial cells during vasculogenesis, as well as for their maintenance and survival throughout the lifetime of blood vessels [23]. However, under subtle pathological alterations, abnormal angiogenesis with retinal and choroidal microvascular alterations have been observed during PDR, high myopia, and neovascular AMD [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…27 Proangiogenic factors have also been verified as targets for treatment of obesity 28 and diabetic retinopathy. 29,30 AMD is characterized by pathological angiogenesis 31 and its treatment has been revolutionized by antiangiogenic agents. 32 In summary, pathological angiogenesis is involved in cancers and various non-neoplastic diseases.…”
Section: Angiogenesis-related Diseasementioning
confidence: 99%